Implementasi Kebijakan Keselamatan dan Kesehatan Kerja (K3) PT. X dalam Proyek Pembangunan Gedung - M. Fachrul A.F; Rr. Vita Nurlatif; Dewi Nugraheni RM (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Construction projects have unique characteristics that differ from other operational activities, as they are time-limited, involve a variety of resources, and require coordination across organizations. Occupational safety and health (K3) is an important element in protecting the workforce as well as the company's assets. This study aims to analyze the implementation of K3 policies in the construction project of PT. X. The research method uses a qualitative approach with case studies, while data analysis is carried out thematically based on the George C. Edwards III policy implementation model, which includes aspects of communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of the K3 policy has been running but has not been optimal. The communication aspect has not been carried out regularly and continuously, resources are still limited with task trapping, the disposition of policy implementers is not evenly distributed, marked by low worker compliance, and the bureaucratic structure has not been supported by standardized SOPs and coordination between work units is still weak. This condition creates a gap between the K3 policy and the implementation in the field, so that it has the potential to increase the risk of work accidents and reduce the effectiveness of labor protection. This research emphasizes the need to strengthen communication, increase resources, implement commitment, and improve the bureaucratic structure to support the implementation of more effective K3 policies.